CURRENT KNOWLEDGE OF METHICILLIN-RESISTANT STAPHYLOCOCCUS AUREUS AND COMMUNITY-ASSOCIATED METHICILLIN-RESISTANT STAPHYLOCOCCUS AUREUS - Matouskova, Ivanka; Janout, Vladimir (Biomedical papers, 2008)
BACKGROUND: Bacterial strains that are oxacillin and methicillin-resistant, historically termed methicillin-resistant Staphylococcus aureus (MRSA) are resistant to all β-lactam agents, including cephalosporins and carbapenems. MRSA are pathogenic and have a number of virulence factors that enable them to result in disease. They are transmissible and important causes of nosocomial infections worldwide. An MRSA outbreak can occur when one strain is transmitted to other patients or through close contacts of infected persons in the community. Hospital-associated MRSA (HA-MRSA) isolates are also frequent causes of healthcare-associated bloodstream and catheter-related infections. Community-associated MRSA (CA-MRSA) isolates are often only resistant to beta-lactam agents and erythromycin but they are an emerging cause of community-associated infections, ecpecially skin and soft tissue infections (SSTI) and necrotizing pneumonia.METHODS: Current possibilities for detecting MRSA strains in the laboratory are reviewed and discussed in the context of the recent literature. RESULTS AND CONCLUSION: The active surveillance and prevention of MRSA occurence and spreading in hospitals are discussed in the context of recent literature.
Keywords: Methicillin resistant Staphylococcus aureus(MRSA)/Community-associated MRSA (CA-MRSA)/Hospital-associated